Analysis of the Dynamics of the Global Business Environment on the Adaptation Strategies of Multinational Companies - Putra Amantha Hasibuan; Sami’an Sami’an; Sarwono Hardjomuljadi; Dharma Teguh Pribadi (International Journal Labs, 2025)
This research analyzes the adaptation strategies of three multinational automotive companies in Indonesia—namely Toyota Motor Manufacturing Indonesia (TMMIN), PT Astra International Tbk., and PT Indomobil Sukses Internasional Tbk.—in responding to the dynamics of the global business environment through the perspective of Dynamic Capability Theory. The focus of the study is directed toward the three components of capability according to the theory: adaptive capability, absorptive capability, and innovative capability, which serve as the basis for evaluating the companies' ability to make strategic adjustments amid rapid changes triggered by globalization, geopolitical tensions, supply chain disruptions, workforce transformation, acceleration of digitalization, and increased global investment in low-emission vehicle technology. The results of the study show that the three companies practice different but complementary adaptation strategies. TMMIN develops the most systemic strategies through electrification, export strengthening, green manufacturing, technology transfer, and triple helix collaboration. Astra's strategy focuses on digital transformation, ecosystem synergy, technology investment, and strengthening corporate sustainability. Indomobil's adaptation strategy focuses on exploiting market knowledge, global brand collaboration, and resilient segments. The synthesis of these three strategies results in an adaptation framework that overcomes the negative impacts of global dynamics, such as supply chain disruptions, skilled labor shortages, technology gaps, and digitalization pressures. This research makes a theoretical contribution to the development of the International Business Management literature, especially in understanding the contextual application of dynamic capability in the Indonesian automotive industry.